The significance of popular proverbs in Algerian folklore (مجلة إحالات, 2026)
Literature has it run weight and value among the arts, and its tool is the language through which it expresses various perceptions and feelings, it is thus a picture of society in all its dimensions.Folk literature is one of the most widespread and common literary genres in world folk literature, as itis present in the cultures of peoples. It is easy to find it in all parts of the world, as it is present among thepeoples of ancient civilizations, as well as among primitives, and also in our technological age.People have been attached to folk literature since ancient times, and have included proverbs andbecome familiar with them, loading them with their ideas, philosophy and beliefs, so it has become a feature through which they communicate with each other, through symbols and expressions to lead the recipient to understand meanings derived from social, economic, political, ideological and cultural reality.This research includes a study of some Algerian proverbs as an example, and summary, in order tounderstend them in light of analysis and statistics, without resorting to an extensive presentation.